2019
DOI: 10.1016/j.celrep.2019.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functional Binding Epitope of V-domain Ig Suppressor of T Cell Activation

Abstract: Highlights d The crystal structure of the human VISTA extracellular domain was determined d VISTA contains two unique disulfides and an extended C-C 0 loop d The epitope of an inhibitor antibody was mapped to a threeresidue surface d The antibody epitope was found to overlap with the VISTA-VSIG3 binding interface

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 42 publications
1
73
0
9
Order By: Relevance
“…Earlier studies by our group demonstrated the www.nature.com/scientificreports/ importance of the R54, F62, and Q63 residues for binding to VSTB112 (Fig. 3c, cyan bars) 12 . We also expanded the panel to include five residues adjacent in 3D space to the mapped SG7 region to probe for locations potentially missed by the yeast screen ( Fig.…”
Section: Sg7 Binds To a Distinct Epitope On Vistamentioning
confidence: 77%
See 2 more Smart Citations
“…Earlier studies by our group demonstrated the www.nature.com/scientificreports/ importance of the R54, F62, and Q63 residues for binding to VSTB112 (Fig. 3c, cyan bars) 12 . We also expanded the panel to include five residues adjacent in 3D space to the mapped SG7 region to probe for locations potentially missed by the yeast screen ( Fig.…”
Section: Sg7 Binds To a Distinct Epitope On Vistamentioning
confidence: 77%
“…In sort 2, remaining mutants that had lost binding to SG7 were screened against 5 nM SG7 for increased stringency. VSTB112 binds a conformational epitope 12 and could therefore be used as a positive control for structural integrity. Thus, to select against mutations that caused protein misfolding, the library was screened with VSTB112 in sort 3 and only clones that retained binding to 100 nM VSTB112 were collected.…”
Section: Sg7 Binds To a Distinct Epitope On Vistamentioning
confidence: 99%
See 1 more Smart Citation
“…VISTA is a transmembrane protein that contains an immunoglobulin variable (IgV)-like fold and shares similarities with B7 family members PD1, PDL1, CD28 and CTLA4 [17]. The extracellular domain of VISTA contains four conserved cysteines that are not present in other B7 family members [17].…”
Section: Vista Structure and Binding Partnersmentioning
confidence: 99%
“…The closest homolog within the B7 family is PD-L1,which shares a modest 23% sequence identity with VISTA. VISTA regulates a broad spectrum of immune responses [10][11][12][13][14][15][16], and is highly expressed on myeloid cells and tumor-infiltrating lymphocytes (i.e., macrophages and myeloid-derived suppressor cells (MDSCs)). It is also expressed on naïve CD4 + and CD8 + T cells, where it negatively regulates Tcell responses.…”
Section: Introductionmentioning
confidence: 99%